DEVELOPMENT OF BLENDED LEARNING MODEL USING WORDPRESS - Muhammad Hifdzi Adini; Harja Santana Purba; R. Ati Sukmawati (FKIP ULM, 2017)
Abstract. In general, the learning process is implemented by using face-to-face model, meaning that participants and teachers are in one place and one time. With this model, usually communication between participants and teachers can be easily implemented. But there are some obstacles that may be faced, such as the lack of time to discuss and the limited space that can be used. To overcome these problems, a model is needed that provides a medium for meeting participants and teachers without limited space and time. The model is known as blended learning. The blended learning model allows participants and teachers to discuss, share material and practice questions on a virtual classroom. The research undertaken is to develop a blended learning model using an analysis of the blended learning implementation framework and the use of Content Management System (CMS) WordPress technology. With this model is expected to be an additional media used to support teaching and learning process. Keywords: blended learning; virtual class; wordpress. Abstrak. Secara umum, proses pembelajaran dilaksanakan dengan menggunakan model tatap muka, artinya peserta dan guru berada di satu tempat dan satu waktu. Dengan model ini, biasanya komunikasi antar peserta dan guru dapat dengan mudah diimplementasikan. Tapi ada beberapa kendala yang mungkin dihadapi, seperti kurangnya waktu untuk berdiskusi dan keterbatasan ruang yang bisa digunakan. Untuk mengatasi masalah ini, diperlukan sebuah model yang menyediakan media untuk bertemu peserta dan guru tanpa ruang dan waktu yang terbatas. Modelnya dikenal sebagai blended learning. Model blended learning memungkinkan peserta dan guru mendiskusikan, berbagi materi dan mempraktikkan pertanyaan di kelas virtual. Penelitian yang dilakukan adalah mengembangkan model blended learning menggunakan analisis kerangka kerja implementasi blended dan penggunaan teknologi WordPress Content Management System (CMS). Dengan model ini diharapkan bisa menjadi media tambahan yang digunakan untuk menunjang proses belajar mengajar. Kata kunci: blended learning; kelas virtual; wordpress.